(untitled) (Research, Society and Development, 2020)
Coronaviruses are a large viral family, whose infections are recognized since 1960, varying from the common cold to more critical respiratory conditions. Regarding coronavirus 2019 (COVID-19), a wide spectrum of neurological manifestations among infected patients were reported, raising concerns whether Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) had tropism for the central nervous system. To clarify these questions, this bibliographic review was carried out by searching for articles based on national and international data during the period from December 2019 to June 2020. Thus, this review summarizes the current evidence on the transmission routes, focusing on the olfactory bulb and the hematogenic pathways, as well as the direct and indirect pathological mechanisms through which SARS-CoV-2 causes neurological damage. Moreover, clinical, laboratorial, and therapeutic aspects to manage patients with COVID-19 related neurological symptoms are outlined. Finally, development of treatments tackling specific structures and pathways related to viral entry and cardiovascular regulation on the brain are expected, in addition to monitoring of patients affected by the COVID-19 to assess long-term consequences on the nervous system.